Controversies in Treating Diabetes Clinical and Research Aspects - Leroith, Derek.; Leroith, Derek.; Vinik, Aaron I.; Vinik, Aaron I. (Contemporary Endocrinology,, 2008)
Diabetes Mellitus is an extremely common disorder and the number of patients is increasing every year. Controversies in Treating Diabetes: Clinical and Research Aspects addresses diabetes controversies, specifically in the etiology and management of the disease. With a thorough examination of the complications associated with diabetes, the volume covers commonly accepted forms of therapies and complications, as well as new and emerging advances, therapies and inadequacies in several standard treatments. Topics of emphasis include the metabolic syndrome, using insulin to treat Type 2, retinopathy, neuropathy, environmental stress, the diabetic foot, incretins, and the ADA and NCEP criteria for treating hyperlipidemia of diabetes. Comprehensive and timely, Controversies in Treating Diabetes: Clinical and Research Aspects is an essential reference for those treating and researching diabetes.